Shortcomings and Risks of Borrowing Funds Through online P2P Lending Applications for Trader - Indrajaya, Sonny; Imaroh, Tukhas Shilul (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2026)
Examining business capital as an important need. The author aims to find out the problems of Information borrowers risk of default, liquidity risk, P2P platforms, fintech in borrowing funds through online P2P loan applications for entrepreneurs other than conventional financial  institutions. This research uses quantitative methods and data testing using the warp pls tool using data from questionnaires conducted by 50 lender as respondents. The results of testing and analyzing this study related to borrower information have an influence on P2P lending, the risk of default has an influence on the P2P lending platform, and liquidity risk has an influence on the P2P lending platform. This research design has limitations from its variables, only involving certain demographics. The number of respondents and characteristics of respondents are still limited. The data analysis technique used in this study is only a quantitative method. The findings can be implemented as a business strategy with good planners and P2P lenders who have a lot of knowledge and are very good. By developing a P2P platform, this study can be more useful for lenders to focus on information about borrowers, default risk, liquidity risk in Jakarta. Business strategies using this model can be used as a model for P2P platforms in Jakarta. This research focuses on the shortcomings and risks of borrowing funds through online P2P lending applications for trader.